International Lending, Sovereign Debt and Joint Liability : An Economic Theory Model for Amending the Treaty of Lisbon - Basu, Kaushik (World Bank, Washington, DC, 2013)
As the Eurozone crisis drags on, it is evident that a part of the problem lies in the architecture of debt and its liabilities within the Eurozone and, more generally, the European Union. This paper argues that a large part of the problem can be mitigated by permitting appropriately-structured cross-country liability for sovereign debt incurred by individual nations within the European Union. In brief, the paper makes a case for amending the Treaty of Lisbon. The case is established by constructing a game-theoretic model and demonstrating that there exist self-fulfilling equilibria, which would come into existence if cross-country debt liability were permitted and which are Pareto superior to the existing outcome.